1996
DOI: 10.1038/381335a0
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and NMR structure of human Bcl-xL, an inhibitor of programmed cell death

Abstract: THE Bcl-2 family of proteins regulate programmed cell death by an unknown mechanism. Here we describe the crystal and solution structures of a Bcl-2 family member, Bcl-xL (ref. 2). The structures consist of two central, primarily hydrophobic alpha-helices, which are surrounded by amphipathic helices. A 60-residue loop connecting helices alpha1 and alpha2 was found to be flexible and non-essential for anti-apoptotic activity. The three functionally important Bcl-2 homology regions (BH1, BH2 and BH3) are in clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
1,135
3
19

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,393 publications
(1,190 citation statements)
references
References 26 publications
31
1,135
3
19
Order By: Relevance
“…42 Early on, X-ray and NMR structural analysis revealed that an important inhibitor of PCD, BCL-x L , contains a 60-residue IDPR connecting helices al and a2. 43 Other members of the BCL-2 family, BH3-only proteins (such as BIM, BAD, and BMF) that serve as key initiators of PCD are largely disordered in solution. 44 Interaction of the disordered BIM, BAD, BMF, BAK, and tBID with several pro-survival BCL-2 family members leads to the formation of an a-helical segment that anchors these BH3-only proteins to the hydrophobic groove of their binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…42 Early on, X-ray and NMR structural analysis revealed that an important inhibitor of PCD, BCL-x L , contains a 60-residue IDPR connecting helices al and a2. 43 Other members of the BCL-2 family, BH3-only proteins (such as BIM, BAD, and BMF) that serve as key initiators of PCD are largely disordered in solution. 44 Interaction of the disordered BIM, BAD, BMF, BAK, and tBID with several pro-survival BCL-2 family members leads to the formation of an a-helical segment that anchors these BH3-only proteins to the hydrophobic groove of their binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins share a similar helical bundle architecture composed of a hydrophobic, helical hairpin surrounded by a sheath of amphiphilic α-helices. Structurally, Bcl-x L ΔTM is most similar to the translocation domain of diphtheria toxin (23). For this toxin, as well as others, membrane association is mediated in part by the so-called hydrophobic, helical hairpin, which corresponds to α-helices 5 and 6 in Bcl-x L ΔTM (Figure 5a) (38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Two Acidic Residues In the Conserved Hairpin And The Conformmentioning
confidence: 99%
“…Because full-length Bcl-x L is anchored to the membrane by its transmembrane domain, experiments with this construct are not ideal for understanding the conformational change that primarily involves the N-terminal domain. Therefore, in this work, we describe experiments with synthetic lipid vesicles and Bcl-x L ΔTM, a construct that retains pro-survival activity in vivo (23). We determine the pH dependence of this process by testing for protein association with lipid vesicles as a function of pH with a sedimentation assay.…”
mentioning
confidence: 99%
“…Since Bcl-2 can in¯uence Ca ++ across membranes (Ba y et al, 1993;Lam et al, 1994), it has been also proposed that Bcl-2 or its family members may be involved in tra cking of ions (Reed 1994). In an analysis of the three-dimensional structure of Bcl-X L , Muchmore et al (1996) demonstrated signi®cant similarity with the pore-forming domains of bacterial toxins and proposed that Bcl-X L or its family members may be involved in regulating ion-channels across membranes. In support of this proposal, Schendel et al (1997) demonstrated the ability of recombinant Bcl-2 to form ion channels using a synthetic lipid bilayer-based assay.…”
mentioning
confidence: 99%